URCP: Universal Rate Control Protocol for Real-Time Communication Applications - Xie, Di; Mehrotra, Sanjeev; Li, Jin; Hu, Y. Charlie (Microsoft Research, 2013)
We present a Universal Rate Control Protocol (URCP), which provides applications with fair and full link utilization while operating at low delay and loss levels as needed by interactive real-time communications (RTC) applications across a range of complex networks in use today, such as Wi-Fi hotspots, 4G (HSPA+), and WiMAX. As opposed to many existing rate control techniques which are specially designed for differing network types and application requirements, URCP attempts to provide a universal framework for rate control by learning network parameters and then automatically adapting a utility maximization based rate control framework to achieve good performance across any network. URCP is able to provide significantly improved performance over state-of-art rate control techniques for RTC applications, in terms of throughput, delay, and loss. On real-world network tests, URCP provides similar throughput to commonly used loss based schemes while achieving up to a 100x improvement in operating delay (compared to TCP NewReno on the Clearwire WiMAX network). Compared to existing delay based rate control protocols commonly used by RTC applications, URCP provides similar operating delay while achieving close to 2.5x improvement in throughput on noisy networks (compared to WebRTC on the T-Mobile HSPA+ network).